Enhancing Data Integrity in Wireless Sensor Networks Using a Base-Station Controlled Clustering Protocol - Khalid Khalis Ibrahim (Indonesian Journal Publisher, 2025)
Wireless Sensor Networks (WSNs) are increasingly used in applications involving environmental monitoring, military applications, and automation in industries. Nonetheless, the networks continue to experience challenges in providing data integrity and network lifetime in situations of resource constraint and security attack. In this study, a new protocol is proposed using BaseStation Controlled Dynamic Clustering Protocol (BCDCP) with Identity-Based Aggregate Signatures (IBAS). The protocol helps the Base Station (BS) choose the best Cluster Heads (CHs) and assign signature aggregation responsibilities to the Deputy Cluster Heads (DCHs), hence balancing the consumption of energy and reducing the communication overhead. The model has been tested using Network Simulator 2 (NS-2) and compared with the typical BCDCP and the Low-Energy Adaptive Clustering Hierarchy (LEACH) protocols. From the simulation results, the proposed scheme is found to reduce authentication overhead by a factor of 25%, improve the Packet Delivery Ratio (PDR) by a factor of up to 30%, and improve the entire network lifetime by a factor of up to 20%. These results illustrate the superiority of the proposed model in the reduction of security and improvement in the efficiency of WSNs in terms of energy consumption